-7(x+1)-3(-5x+1)=6

Simple and best practice solution for -7(x+1)-3(-5x+1)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(x+1)-3(-5x+1)=6 equation:



-7(x+1)-3(-5x+1)=6
We move all terms to the left:
-7(x+1)-3(-5x+1)-(6)=0
We multiply parentheses
-7x+15x-7-3-6=0
We add all the numbers together, and all the variables
8x-16=0
We move all terms containing x to the left, all other terms to the right
8x=16
x=16/8
x=2

See similar equations:

| -3v-31=-2(3v+8) | | 9y-29=-119 | | 3n+3(-5n-2)=7+n | | 2.5d+10.25=8+3.25d | | 18x+6x+6x= 180° | | 2x-2=-2(1-3x)+7x | | 3(x-4)+6=7x+10 | | 3n-40=5(1+5n)-1 | | 90+(4x+3)+x+7)+(3x)=180 | | 2=6-m | | k+7.2=3.2 | | 17=7-k | | y=114-3y | | y+5=6y-10 | | -3-5(1-5x)=-7x+24 | | 12b+3-3b+8=44 | | s-$10=$20.92 | | 13s-8s=20 | | 49=6y-5 | | -9=9(w-8) | | 9-6y=-42 | | 12y-11y=19 | | 15-x=-7(x+3) | | 5/8x+1/3=69 | | 9(x)=1/2x-3;9(x)=-4 | | t/3-11=13 | | t/3-11=-3 | | v-5=-3(v-1) | | 180=12x+30 | | -3=9-3d | | 3(2x+2)−3x=6+3x | | 2-32/3p=91/3 |

Equations solver categories